Improved outcomes utilizing a novel pectin-based pleural sealant following acute lung injury. Issue 5 (November 2020) - Kuckelman, John; Conner, Jeffrey; Zheng, Yifan; Pierce, Aidan; Jones, Ian; Lammers, Daniel; Cuadrado, Dan; Eckert, Matthew; Mentzer, Steven
Abstract : BACKGROUND: Persistent air leaks after thoracic trauma are associated with significant morbidity. To evaluate a novel pectin sealant in a swine model of traumatic air leaks, we compared a pectin biopolymer with standard surgical and fibrin-based interventions. METHODS: A standardized lung injury was created in male Yorkshire swine. Interventions were randomized to stapled wedge resection (n = 5), topical fibrin glue (n = 5), fibrin patch (n = 5), and a pectin sealant (n = 6). Baseline, preintervention and postintervention tidal volumes (TV) were recorded. Early success was defined as the return to near-normal TV (>95% of baseline). Late success was defined as no detectable air leak in the chest tube after chest closure. RESULTS: There were no differences in injury severity between groups (mean TV loss, 62 ± 17 mL, p = 0.2). Early success was appreciated in 100% (n = 6) of the pectin interventions which was significantly better than the fibrin sealant (20%, n = 1), fibrin patch (20%, n = 1), and stapled groups (80%, n = 4, p = 0.01). The percent of return to baseline TV after sealant intervention was significantly increased in the pectin (98%) and staple arms (97%) compared with the fibrin sealant (91%) and fibrin patch arms (90%) ( p = 0.02; p = 0.03). Late success was also improved with the pectin sealant: no air leak was detected in 83% of the pectin group compared with 40% in the stapled group ( p = 0.008)—90% of the fibrin-based interventions resulted in continuous air leaks ( p = 0.001). CONCLUSION: Pectin-based bioadhesives effectively seal traumatic air leaks upon application in a porcine model. Further testing is warranted as they may provide a superior parenchymal-sparing treatment option for traumatic air leaks.